Intramuscular injection of human umbilical cord-derived mesenchymal stem cells improves cardiac function in dilated cardiomyopathy rats. Issue 1 (December 2017) - Mao, Chenggang; Hou, Xu; Wang, Benzhen; Chi, Jingwei; Jiang, Yanjie; Zhang, Caining; Li, Zipu
Abstract Background Stem cells provide a promising candidate for the treatment of the fatal pediatric dilated cardiomyopathy (DCM). This study aimed to investigate the effects of intramuscular injection of human umbilical cord-derived mesenchymal stem cells (hUCMSCs) on the cardiac function of a DCM rat model. Methods A DCM model was established by intraperitoneal injections of doxorubicin in Sprague-Dawley rats. hUCMSCs at different concentrations or cultured medium were injected via limb skeletal muscles, with blank medium injected as the control. The rats were monitored for 4 weeks, meanwhile BNP, cTNI, VEGF, HGF, GM-CSF, and LIF in the peripheral blood were examined by ELISA, and cardiac function was monitored by echocardiography (Echo-CG). Finally, the expression of IGF-1, HGF, and VEGF in the myocardium was examined by histoimmunochemistry and real-time PCR, and the ultrastructure of the myocardium was examined by electron microscopy. Results Injection of hUCMSCs markedly improved cardiac function in the DCM rats by significantly elevating left ventricular ejection fraction (LVEF) and left ventricular fraction shortening (LVFS). The BNP and cTNI levels in the peripheral blood were reduced by hUCMSCs, while HGF, LIF, GM-CSF, and VEGF were increased by hUCMSCs. Expression of IGF-1, HGF, and VEGF in the myocardium from the DCM rats was significantly increased by hUCMSC injection. Furthermore, hUCMSCs protected the ultrastructure of cardiomyocytes by attenuating mitochondrial swelling and maintaining sarcolemma integrity. Conclusions Intramuscular injection of UCMSCs can improve DCM-induced cardiac function impairment and protect the myocardium. These effects may be mediated by regulation of relevant cytokines in serum and the myocardium.